In other Los Angeleses : multicentric performance art - Cheng, Meiling, 1960- (Berkeley : University of California Press, 2002)
Performance art and Los Angeles, two subjects spectacularly resistant to definitions, illuminate each other in this searching study by Meiling Cheng. A marginal artistic pursuit by choice as well as necessity, performance art has flourished in and about "multicentric" Los Angeles for nearly four decades, finding its own centers of activity, moving and changing as the margins have reconstituted themselves.
Illustrations; Preface; Acknowledgments; 1: Inscribing Multicentricity: Performing Other Los Angeleses; 2: Out of Order: Reading, Writing, Performing (in) L.A.; 3: Engendering Other/Selves: Suzanne Lacy; 4: Elia Arce: A Skin Test and a Tongue Transplant; 5: A Hetero-locus in Process: Self Performances at Highways; 6: What's in a Name?: Marking Sacred Naked Nature Girls; 7: Kinesthetic Transmutation of Theatricality: Consuming Art Performances; Epilogue; Notes; Index.
"Published in association with the Southern California Studies Center of the University of Southern California."
Includes bibliographical references (pages 353-392) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Performance art -- California -- Los Angeles; Manœuvre artistique -- Californie -- Los Angeles; ART -- Reference; ART -- Performance; PERFORMING ARTS -- Film & Video -- General; Performance art; California -- Los Angeles; Arts du spectacle -- États-Unis -- Los Angeles; Géographie culturelle -- États-Unis -- Los Angeles; Humaniora -- Kunst